The implementation of the ROC weighting method on EDAS for optimizing employee incentive distribution (Case Study of PT. Juishin) - Simanungkalit, Ahmad Hazazi; Al-Khowarizmi; Faradillah, Yanty (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2025)
Rewards can serve as a tool for motivating employees within a company. Typically, companies offer rewards to employees in the form of salary increases, incentives or bonuses, promotions, and other rewards, similar to those implemented by PT. Juishin. PT. Juishin is a company engaged in the production of cement and ceramics. In awarding rewards, PT. Juishin currently employs a direct selection method, which has led to instances of employee dissatisfaction. This research aims to design and develop an application for the selection of employees eligible for rewards by utilizing the ROC and EDAS methods. The application of these methods will facilitate the company's process of selecting reward recipients. The system design employs UML, including use case diagrams, activity diagrams, class diagrams, and sequence diagrams. The outcome of this research is to assist HR in determining the eligibility of reward recipients. The application will display the ranking process of reward recipients, where those with the highest scores will receive the rewards. The system testing is conducted using black box testing to ensure that the application meets the functional requirements. The result of this research will assist the company in assessing employee eligibility for rewards on a daily basis.